A high preoperative serum IL-25 level is a negative prognosis predictor after liver resection for HBV-HCC - Chen, Shao-hua; Wang, Xu (Frontiers in Oncology, 2022)
Objective: To assess the importance of preoperative platelet count for IL-25 in patients with HBV-HCC after liver surgery. Methods: Between 2008 and 2015, this retrospective study enrolled consecutive HCC patients who underwent liver surgery. Baseline clinical and pathological characteristics were analyzed to determine predictors of disease-free and overall survival of patients after liver resection. Immunoassays were performed to assess serum IL-25 levels. Results: Univariate and multivariate analyzes using the Cox regression model showed that IL-25 was an independent factor influencing relapse and overall survival in 896 patients with HBV-associated HCC. The optimal cutoff of IL-25 using the receiver performance curve was 14.9 μg / ml. There were 206 patients who had an IL-25 of 14.9 mcg / ml or more. Survival rates of RFS and OS after liver resection were better in patients with anIL-25 <14.9 μg / L compared with patients with anIL-25 of 14.9 μg or more (P <0.05). Cox multivariate regression analysis showed that IL-25 ≥14.9 μg / L was an independent predictor of the risk of worse RFS and OS. IL-25 in combination with tumor diameter may be the best predictor of OS. Conclusions:IL-25 played the role of an independent factor for predicting survival after hepatectomy in patients with HCC.